The opinions of nurses regarding low adherence to standard precautions to prevent healthcare acquired infections - Mmereki, Kenneth (My University, 2018)
The purpose of this study was to explore the opinions of nurses as to why there was a low adherence to standard precautions (SP) of infection control , ways in which adherence might be improved and to make some suggestions to the Infection Prevention and Control policies and practice at an academic hospital. This study used a qualitative exploratory design. The population comprised of all Registered nurses (RNs) and Enrolled nurses working in the postnatal ward, general paediatric ward, medical ward, general surgical ward and general wards. Purposive sampling was used and the sample size was 28 (n = 28) .The self-administered narrative sketches were used as the data collection tool. This study employed directed content analysis in which the findings of the study were grouped independently and compared to findings of previous studies. The participants reaffirmed poor basic training, risk behaviours, inadequate provision of equipment and protective equipment and inappropriate work conditions as reasons for low adherence to Standard Precautions among nurses. Lack of skills and knowledge regarding standard precautions can lead to non-adherence. Behavioural and cognitive skills of individuals were associated with the low adherence to Standard Precautions. The study found that insufficient supply of resources, use of uncomfortable personal protective equipment, excessive workload, lack of time, high numbers of patients and shortage of nurses, all contribute to non-adherence to standard precautions among nurses. The findings of the study do not support unawareness of the importance of standard precautions as a reason for low adherence to SPs. Most participants felt that the level of adherence to standard precautions among nurses was satisfactory. Nurses recommended continuous education, regular audits, motivation, increasing numbers continuous support visits and use of reminders. Recommendations to the policies of Infection Control at the hospital include continuing professional development/education, regular supply of Personal Protective Equipment, Institutional strategies to change risk behaviours, management support. Further research should be conducted to examine strategies to address barriers found in this study.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2018.
Keywords: Standard Precautions; Infection Control